ON THE QUESTION OF PREDICTING THE SERVICE LIFE OF LATTICE STEEL STRUCTURAL ELEMENTS - Emelianov, Oleg Vladimirovich; Shuvalov, Alexander Nikolaevich; Prokic, Milan (Journal of Applied Engineering Science, 2017)
Present paper deals with the evaluation of fatigue strength at crack initiation stage in the double angle elements of lattice steel structures. The current construction norms for steel structures do not include check for fatigue strength at crack initiation stage, and the calculation of elements endurance limit does not account actual stress-strain state in stress concentration zones, material deformation characteristics in these areas, and strength properties of steel. Experimental study of the stress-strain state kinetics in the areas of gusset plate breakage of double angle welded joints was carried out by strain gauge method. Results were obtained regarding the stress state stabilization under cyclic loading and stress intensity factor. During cyclic tests, maximum load level varied depending on the yield stress. The formation of fatigue cracks was detected in the zone of gusset plate breakage. The curve at fatigue cracks initiation stage, by deformational fracture criteria at "stiff" loading, was described by the equations presented in the "Standards of strength calculation of equipment and pipelines of nuclear power plants". Calculation analysis of results for number of cycles before fatigue crack initiation has been made and good agreement with test results has been obtained.
Keywords: Steel lattice structures; Fatigue crack; Fatigue strength; Elastoplastic deformation of the material; Deformation fracture criterion; stress intensity factor; cyclic loading